2015
DOI: 10.3923/ijzr.2015.188.197
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Genetic Diversity of Two Black Fly Species (Diptera: Simuliidae) from South India using DNA Barcode Based RFLP Analysis

Abstract: The population genetic diversity of two black fly species (S. (S.) gurneyae and S. (S.) nilgiricum) was investigated along an elevational gradient in two hills of South India by mitochondrial gene sequence of cytochrome coxidase subunit I (COI) based Restriction Fragment Length Polymorphism (RFLP). By comparing the similarity of the bands produced by three restriction endonuclease enzymes, the genetic distance was calculated among sampling sites. The mean Kimura two parameter divergences of two black fly speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…This result indicated that only one restriction site on the COI gene of S. commersonnii was recognized by that enzyme. Our result similar to previous study from Arunprasanna et al (2015) on Simulium gurneyae and Simulium nilgirium although with different sizes (468 bp and 241 bp). This similarity indicates that the same partial sequences of COI gene in different species has similar restriction site for VspI although amplified from different species.…”
Section: Resultssupporting
confidence: 92%
“…This result indicated that only one restriction site on the COI gene of S. commersonnii was recognized by that enzyme. Our result similar to previous study from Arunprasanna et al (2015) on Simulium gurneyae and Simulium nilgirium although with different sizes (468 bp and 241 bp). This similarity indicates that the same partial sequences of COI gene in different species has similar restriction site for VspI although amplified from different species.…”
Section: Resultssupporting
confidence: 92%